Potencial alelopatico de Inga marginata W. e seus efeitos sobre o desenvolvimento de milho: a viabilidade para sistemas agroflorestais - Luz, Ezequiel Marçal Zanchetti da (2018)
In the first chapter the objective was to evaluate in laboratory the allelopathic effect of the aqueous extract of ingá leaves on germination, initial development and antioxidant activity of maize seedlings and in the second chapter the objective was to evaluate in greenhouse the allelopathic effect of the ingá on the emergency, initial growth and antioxidant response of corn seedlings. For the allelopathic effect on germination, we analyzed the percentage of germination, germination speed index, mean germination time, frequency and synchronization of the germination of the maize seeds exposed to the different proportions of the aqueous extract of the dried leaves of ingá. For the effect on the initial development, we analyzed the weight of the dry mass and the average length of the roots and aerial parts of the maize seedlings. The enzymes involved in oxidative stress, Superoxide dismutase, Catalase and Peroxidase, as well as lipid peroxidation, measured by the levels of malondialdehyde (MDA), were also quantified. For the greenhouse emergency test the treatments were also constituted by the different proportions of the aqueous extract of ingá, being evaluated the percentage of emergency, average time of emergency, index of emergency speed, synchronization and relative frequency. In the initial greenhouse growth test, a control was obtained and the treatment two that received ground cover with dry leaves of ingá, evaluating the aerial part dry mass, root dry mass, average length of aerial part and length root mean. For the evaluation of oxidative stress on initial growth, enzymes, superoxide dismutase, peroxidase and catalase, besides lipid peroxidation by malondialdehyde levels were quantified. The aqueous extract of the ingá leaves did not interfere in the germination variables of the corn, however, caused inhibition of root mean length, inhibited root and shoot catalase activity and increased root MDA contents. There were no statistical differences between treatments for the variables evaluated in the emergence and initial growth of corn seedlings in greenhouse. However, we observed that there was greater expression of catalase in both root and aerial part and lower lipid peroxidation in the aerial part of the seedlings submitted to treatment two. In this way we propose that the consortium among the species in Saf's is viable.